2021
DOI: 10.1177/10848223211038510
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Barriers to the Development of Home Health Care in Iran: A Qualitative Study

Abstract: Changes in society’s needs have increased individuals’ desire to be independent and receive health care at home. Home health care (HHC) is one of the main components of realizing these ambitions. However, there is a serious concern about the state of development of the HHC industry in Iran and the quality of its services. This study aims to explore the barriers to the development of HHC in Iran. This qualitative study with a conventional content analysis approach was conducted in Tabriz, Iran, from October 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Another challenge is the high cost of health service provision in the community in the form of home visits and the fact that they are not paid by insurance. Allocating less funds for providing community-based care than for treatment care and hospitalization is another challenge in the Iranian health system ( 16 , 17 , 31 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another challenge is the high cost of health service provision in the community in the form of home visits and the fact that they are not paid by insurance. Allocating less funds for providing community-based care than for treatment care and hospitalization is another challenge in the Iranian health system ( 16 , 17 , 31 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that legislators prioritize accountability principles based on community, justice, and accessibility. In addition, policymakers need to develop a strategy to reform policies in order to lay the ground for the development of nursing at the community level ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It must be noted that home care is completely a new sector in Iran, and despite its remarkable improvements, there is still room for planning and improvement [ 39 ].…”
Section: Discussionmentioning
confidence: 99%